Saltwater intrusion as potential driver of phosphorus release from limestone bedrock in a coastal aquifer. (5th January 2017) - Flower, Hilary; Rains, Mark; Lewis, David; Zhang, Jia-Zhong; Price, René
Abstract: An important but often overlooked consequence of saltwater intrusion is the potential increase of groundwater soluble reactive phosphorus concentrations. The phosphorus sorption dynamics of two limestone rocks of different composition were investigated by simulating seawater intrusion over a wide range of mixing ratios between freshwater and saltwater. Both rocks exhibited a logarithmic loss of sorption efficiency in mixtures containing more than approximately 3 mM Cl − concentration (100 mg Cl − /L; about <1% saltwater). We infer that aquifer solids immersed in freshwater would undergo phosphorus desorption in response to the introduction of this minor amount of seawater. This Cl − concentration is within the range designated as fresh water. Thus we conclude that increased soluble reactive phosphorus availability from saltwater-induced desorption may occur at the ion exchange front, which is actually landward of the saltwater intrusion front as it is commonly defined. Sorption efficiency in our experiments continued to decline as salinity increased, until Cl − concentration reached a second threshold of 50 or 200 mM (1700 or 7700 mg Cl − /L), depending on the rock composition, particularly iron content. Further increase in salinity would produce little increase in groundwater soluble reactive phosphorus concentration. Our results have implications for soluble reactive phosphorus availability in estuaries that receive mixing zone groundwater discharge.